Personality Aspect In The Supernova Novel Particle Episode By Dee Lestari - I Wayan Mawa; Ni Putu Parmini; Ida Ayu Putu Aridawati; Ida Bagus Rai Putra; I Gede Bagus Wisnu Bayu Temaja; Ni Luh Anik Febrianti (Cita konsultindo, 2023)
This study aims to analyze aspects of the main character’s personality and the factors that influence the main character’s personality in the novel Supernova Episode Particle by Dee Lestari using academic psychology. The theory used in finding the main character’s personality was the Heymans theory. The method used was descriptive qualitative. The data were obtained from books related to this research, both theoretical and factual data from the novel Supernova Episode Particle. The data collection method used in this research was the library method. The data were analyzed using data triangulation, in which there are several steps, namely: data collection, data reduction, data presentation, and conclusion. This study found data that supports the research focus, namely aspects of the main character’s personality and the factors that influence the main character’s personality. The study results found that Zarah, as the main character, has a personality that tends to be passionate, phlegmatic and choleric. Factors that influence Zarah’s personality are genetic, environmental, cultural, and experience factors.